Cancer Research UK Centre for Drug Development: translating 21st-century science into the cancer medicines of tomorrow. Issue 8 (August 2015) - Ritchie, James W.A.; Williams, Robert J.
Highlights CRUK Centre for Drug Development is a non-commercial cancer drug development resource. It provides a unique route for development of academic and commercial cancer drugs. Has developed innovative business models encouraging industry/academic partnerships. Over 130 early Phase trials have been delivered on 120 different novel cancer drugs. Five of these drugs are currently approved for treating various forms of cancer.